Knowledge, attitude, and perception towards halal medicines among health sciences students: an insight from a Malaysian public university - Elsayed, Tarek Mohamed Ali; Azhar, Nur Ayisy Liyana; Ahmed Osman, Ahmed Mohamed Yehia Naguib; Nahas, Abdul Rahman Fata; Al-Shami, Abdulkareem Mohammed (SAGE Publications, 2025)
Healthcare sciences students as a future healthcare professionals should be ready to play their role in raising awareness about Halal Pharmaceuticals and meet patient’s expectations. This study aimed to evaluate the knowledge, attitude, and perception (KAP) of health sciences students towards Halal Pharmaceuticals and their association with respondents’ demographics. A structured self-administered online questionnaire was used for data collection. The majority of respondents were female (71%), Malay (91%) and Muslims (92.3%). The average scores above 80% in all domains reflected a high knowledge about Halal medicines as well as a positive attitude and perception towards them. Several demographic factors, most notably receiving education about Halal Medicines, were associated with statistically significant differences in all or some of the domain scores. A statistically significantly higher knowledge about Halal Medicines was associated with receiving education about it, Malay race and Islam religion (p = .029, .005 and .013, respectively) and lower among dietetic program students (p = .000). A statistically significantly higher attitude as a healthcare professional and a consumer was associated with the age below 24 years, pharmacy program, first year of study, Malay race, Islam religion and receiving education about Halal Medicines (p = .028, .003, .039, .004, .004 and .0021, respectively). A statistically significant higher perception score as a healthcare professional is associated with lower age, pharmacy program, Islam religion and education about Halal Medicines (p = .018, .003, .044 and .006, respectively). The results generally revealed respondents’ good knowledge about Halal Pharmaceuticals with positive attitude and perception towards them. Non-Muslim students tend to be more neutral in their perception and attitude and less knowledgeable about the items that are considered non-Halal. Emphasis on integration of Halal medicinerelated topics in the curriculum is essential to avoid such weaknesses.